Overview of cellular homeostasis-associated nuclear envelope lamins and associated input signals - Kim, Hyeong Jae; Lee, Peter C. W.; Hong, Jeong Hee (Frontiers in Cell and Developmental Biology, 2023)
With the discovery of the role of the nuclear envelope protein lamin in human genetic diseases, further diverse roles of lamins have been elucidated. The roles of lamins have been addressed in cellular homeostasis including gene regulation, cell cycle, cellular senescence, adipogenesis, bone remodeling as well as modulation of cancer biology. Features of laminopathies line with oxidative stress-associated cellular senescence, differentiation, and longevity and share with downstream of aging-oxidative stress. Thus, in this review, we highlighted various roles of lamin as key molecule of nuclear maintenance, specially lamin-A/C, and mutated LMNA gene clearly reveal aging-related genetic phenotypes, such as enhanced differentiation, adipogenesis, and osteoporosis. The modulatory roles of lamin-A/C in stem cell differentiation, skin, cardiac regulation, and oncology have also been elucidated. In addition to recent advances in laminopathies, we highlighted kinase-dependent nuclear lamin biology and recently developed modulatory mechanisms or effector signals of lamin regulation. Advanced knowledge of the lamin-A/C proteins as diverse signalling modulators might be biological key to unlocking the complex signalling of aging-related human diseases and homeostasis in cellular process.